In Vivo Two Photon Imaging of Astrocytic Structure and Function in Alzheimer’s Disease - Kelly, Patricia; Hudry, Eloise; Hou, Steven S.; Bacskai, Brian J. (Frontiers in Aging Neuroscience, 2018)
The physiological function of the neurovascular unit is critically dependent upon the complex structure and functions of astrocytes for optimal preservation of cerebral homeostasis. While it has been shown that astrocytes exhibit aberrant changes in both structure and function in transgenic murine models of Alzheimer’s disease (AD), it is not fully understood how this altered phenotype contributes to the pathogenesis of AD or whether this alteration predicts a therapeutic target in AD. The mechanisms underlying the spatiotemporal relationship between astrocytes, neurons and the vasculature in their orchestrated regulation of local cerebral flow in active brain regions has not been fully elucidated in brain physiology and in AD. As there is an incredible urgency to identify therapeutic targets that are well-tolerated and efficacious in protecting the brain against the pathological impact of AD, here we use the current body of literature to evaluate the hypothesis that pathological changes in astrocytes are central to the pathogenesis of AD. We also examine the current tools available to assess the structure and function of astrocytes within the living murine brain in health and in AD.